1991
DOI: 10.1002/j.1460-2075.1991.tb07996.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the acetate operon in Escherichia coli: purification and functional characterization of the IclR repressor.

Abstract: Growth of Escherichia coli on acetate requires operation of the anaplerotic sequence known as the glyoxylate bypass. In this pathway three different enzymes are activated: malate synthase, isocitrate lyase and isocitrate dehydrogenase kinase/phosphatase which are encoded by genes aceB, aceA and aceK, respectively. These three genes are clustered, in that order, in the same acetate (ace) operon whose expression is under the transcriptional control of the iclR gene located downstream from aceK. We have cloned th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 33 publications
2
62
0
Order By: Relevance
“…2). The open reading frame of the IclR gene (Sunnarborg et al, 1990;Negre et al, 1991) predicts a protein with a mass of 29,739.3 u, or 29,608.1 if the initial methionine has been removed (see Fig. I), so it was clear that the protein we had isolated was truncated in some way.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2). The open reading frame of the IclR gene (Sunnarborg et al, 1990;Negre et al, 1991) predicts a protein with a mass of 29,739.3 u, or 29,608.1 if the initial methionine has been removed (see Fig. I), so it was clear that the protein we had isolated was truncated in some way.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7 shows that, under these conditions, IclR (0.2-1 mg/mL) elutes from Sephadex G-100 (20 mM Tris-C1, pH 7.8, 0.4 M KCI, 1 mM EDTA, 50 mM &ME) as a tetramer (M, -117,000). Negre et al (1991) found that their IclR preparation sedimented in a sucrose density gradient with a sedimentation coefficient consistent with a dimer (M, -60,000). Together these several results show that freshly prepared lclR is a tetramer at 1 9 0 2 0 0 2 1 0 2 2 0 230 2 4 0 2 5 0 2 6 0 wavelength (nrn) complexes by Orchard and May (1993).…”
Section: Spectroscopic Properties Of Iclr Protein and Native Moleculamentioning
confidence: 97%
See 1 more Smart Citation
“…Binding of IclR to sequences upstream of iclR was tested by gel shift analysis. IclR was overexpressed and purified by a modification of the method described by Cortay et al (4). The probe (1 ng) included sequences from Ϫ152 to ϩ3 relative to the translational start site and was labeled with [␥-32 P]ATP and T4 polynucleotide kinase.…”
mentioning
confidence: 99%
“…The IclR binding site was identified by DNase I footprint analysis. IclR was overexpressed and purified by a modification of the method described by Cortay et al (4). DNase I footprint analysis of the IclR-DNA complex was carried out by a modification of the method described by Shih and Towle (27).…”
mentioning
confidence: 99%